Strain transfer theory of industrialized optical fiber-based sensors in civil engineering: A review on measurement accuracy, design and calibration - Wang, Huaping; Xiang, Ping; Jiang, Lizhong (Sensors and actuators. A. Physical., 2019)
Optical fiber sensors are the most promising technique in monitoring physical and chemical variables of civil structures. For the brittle material characteristics, a bare sensing fiber is prone to breakage under the shear or torsional action existed in the construction and operation. To guarantee the survival and long-term service of the sensors, the packaging measure is particularly significant. This treatment generates an intermedium layer between the sensing fiber and the monitored structure, which leads to the strain of the host material not entirely transferred to the sensing fiber for a portion of strain loss in the transferring path. To correct the error and improve the measurement accuracy, strain transfer theory is developed to establish the quantitative strain relationship between the sensing fiber and the host material. A state-of-the-art review on strain transfer theory of optical fiber based sensors developed for civil structures is addressed. It aims to demonstrate the advance, the application and the challenge of strain transfer theory and provide scientific guidance for the better understanding of the multi-layered sensing model and the theoretical instruction for the optimum design, calibration and measurement accuracy enhancement of optical fiber sensors.